Understanding the development of young children in Singapore : insights from the analysis of Singapore Health Booklet items from the IED-III norming sample - Kan, Delia Dang Dang (2017)
Purpose: Norms stated in the Singapore Health Booklet were established almost 30 years ago using Denver Developmental Screening Test (DDST) Singapore. Thus this study aimed to find out 90th percentile age norms (PAN) of developmental milestones from the Booklet matched to items in Brigance Inventory of Early Development (IED) III of the children of today, and investigate possible reasons for differences observed.